Nilai Nutrisi Dan Kecernaan Nutrien Rumput Odot (Pennisetum Purpureum Cv. Mott) Pada Jarak Tanam Berbeda - HENDRIKUS KILIMANDANG; Hambakodu, Marselinus (JURNAL PETERNAKAN SABANA, 2025)
This experimen aims to determine the effect of planting distance for Odot grass (Pennisetum Purpureum Cv. Mott) on production, nutritional value and nutrient digestibility. This experimen was conducted at the Wira Wacana Sumba Christian University Field Laboratory, Kuta Village, Kanatang District, East Sumba Regency. The experimental design used in this experimen was a Completely Randomized Design (CRD) consisting of 4 treatments and 4 replications as follows: JK1: Odot Grass Planting Distance 40x40cm, JK2: Odot Grass Planting Distance 40x60cm, JK3: Odot Grass Planting Distance 40x80cm, JK4: Odot grass planting distance 40x100cm. The experimen variables are fresh weight production, nutritional value and dry matter digestibility and in vitro digestibility of organic matter. The results showed that planting distance had a significant effect (p<0.05) on fresh produce production. The nutritional value for all treatments had an average DW of 85.99%, Ash 23.97%, BO 76.02%, PK 10.05%, LK 1.56%, SK 19.57% and an average dry matter digestibility of 66.32 % and organic matter 70.30%. In conclusion, Odot grass planting distance of 40 x 40 cm can increase fresh weight production by 2402.50 grams, while the nutritional value of BK is 84.59%, PK 10.01%, SK 21.16%, LK 0.41%, Ash 22.62 %, and dry matter digestibility 63.64%, organic matter digestibility 66.79%.